DOI: 10.11606/t.64.2009.tde-04042011-142159
|View full text |Cite
|
Sign up to set email alerts
|

Fertilidade do solo, nutrição e crescimento de plantas de eucalipto ao longo de 46 meses após aplicação de lodo de esgoto

Abstract: Paulo (FAPESP), pelo auxílio à pesquisa; À FINEP/MCT, pelo apoio financeiro para realização dos analises laboratoriais; À Suzano Bahia Sul Papel e Celulose S.A., pelo apoio com a área experimental, logística de trabalho, especialmente a José Luiz Gava e Fernando Marcio da Silva, pelo constante apoio durante o desenvolvimento do trabalho; Aos funcionários da TECPAR, pelo apoio durante as coletas de campo, especialmente ao amigo Marcos pela grande amizade; Aos prof.Drs. Antonio Enedi Boaretto, Takashi Muraoka e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
2
0
2
Order By: Relevance
“…Notwithstanding, application of the recommended sludge dose alone resulted in a wood volume approximately 99% of that using mineral NPK fertilizers (Table 6), due to soil fertility improvement. The contents (surface A p horizon) of total N, organic C, resin extractable P, K, Ca and Mg, and DTPA extractable and semi-total Cu, Fe, Mn and Zn in the soil increased as a function of sludge application dose, besides leaf litter, for up to 44 months of sludge application (Maldonado, 2009). Under these conditions, nutrient and water uptake and use by Eucalyptus plants are more efficient (Bouillet et al, 2002;Silva et al, 2013;Stape et al, 2006).…”
Section: Recommendations For Using Sewage Sludge Together With Mineramentioning
confidence: 96%
See 1 more Smart Citation
“…Notwithstanding, application of the recommended sludge dose alone resulted in a wood volume approximately 99% of that using mineral NPK fertilizers (Table 6), due to soil fertility improvement. The contents (surface A p horizon) of total N, organic C, resin extractable P, K, Ca and Mg, and DTPA extractable and semi-total Cu, Fe, Mn and Zn in the soil increased as a function of sludge application dose, besides leaf litter, for up to 44 months of sludge application (Maldonado, 2009). Under these conditions, nutrient and water uptake and use by Eucalyptus plants are more efficient (Bouillet et al, 2002;Silva et al, 2013;Stape et al, 2006).…”
Section: Recommendations For Using Sewage Sludge Together With Mineramentioning
confidence: 96%
“…High forest wood production depends, in addition to water and nutrient availability, on the maintenance of the tree canopy's ability to intercept a high proportion of solar radiation (Forrester, 2013;Gonçalves et al, 2004). The increase in Eucalyptus wood production as a function of sludge dose was also related to leaf area index (LAI) and the amount of litter on the soil surface (Firme, 2009;Maldonado, 2009), as they are indicative parameters of forest production quality. We have observed that the higher the sludge dose, the higher the LAI, amount of litter and both N and P accumulation in shoots of the Eucalyptus plants (paper in process).…”
Section: Recommendations For Using Sewage Sludge Together With Mineramentioning
confidence: 99%
“…Esta tendência vem ocorrendo porque estes resíduos industriais estão sendo produzidos com menos contaminantes devido às mudanças no processo de fabricação (Harrison, et al, 2003). Vários estudos têm mostrado que o dregs, cinza e o lodo de esgoto, quando aplicados de forma isolada, trazem benefícios agronômicos às culturas -relacionados ao aumento e, ou, manutenção dos níveis de fertilidade do soloem função do fornecimento de nutrientes ou por meio de alterações em seus atributos químicos (Guerrini, et al, 2000;Harrison, et al, 2003;Rocha, et al, 2004;Corrêa et al, 2007;Lira, et al, 2008;Maldonado, 2009). Por outro lado são poucos os estudos para avaliar os benefícios agronômicos do composto orgânico produzido a partir da mistura dos resíduos gerados no processo de produção de celulose e papel.…”
Section: Introductionunclassified
“…Também observou-se efeito significativo (p ≤ 0,10) de LE e de fósforo sobre o volume de madeira com casca para este experimento aos 43 e 44 meses pós plantio de Eucalyptus grandis respectivamente (FIRME, 2009;MALDONADO, 2009). Assim, nota-se que a tendência de respostas da produção de madeira manteve o efeito para a fertilização mineral fosfatada e à aplicação de LE.…”
Section: 035 ---------------% ----------------unclassified